Perbandingan Kepuasan Mahasiswa pada Pelaksanaan Kuis dengan Metode Konvensional dan Kahoot! Aplikasi - Ferdinan Sihombing; Yuanita Ani Susilowati; Elizabeth Ari Setyarini (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; quizzes are needed to increase student motivation to learn and assess their understanding of the course material. Quizzes can take the form of conventional tests (paper-based tests) and can use information technology, for example, the